COMMUNITY EMPOWERMENT THROUGH PRODUCT INNOVATION AND UTILIZATION OF DIGITAL TECHNOLOGY TO INCREASE EFFICIENCY, PRODUCTIVITY, AND PROMOTION OF MSMES IN TANJUNGSARI VILLAGE IN THE ERA OF SOCIETY 5.0 - Wahanani, Henni Endah; Sukirmiyadi, Sukirmiyadi (Universitas Airlangga, 2025)
Tanjungsari Village, Panekan District, Magetan Regency, East Java has been known as a rabbit village since the 1980s and has won a national award as a rabbit center from President Soeharto in 1985. However, Micro, Small, and Medium Enterprises (MSMEs) in this village face several obstacles, including low innovation in rabbit-based processed products, unattractive product packaging, and limitations in utilizing digital technology for marketing. PKM IMRIS aims to increase the capacity of MSMEs through a participatory approach with training in innovation in processed rabbit floss products, development of packaging designs, and utilization of digital platforms such as the Shopee marketplace and social media for promotion and sales. Activities are carried out through lectures, training, and intensive mentoring. The results of the program show a significant increase in partner skills, both in producing innovative processed products and packaging, and in utilizing digital technology to expand market reach. This program has succeeded in making partners competitive digital innovation and marketing agents, as well as strengthening the identity of Tanjungsari Village as a center for superior rabbit-based products. of UMKM products in Tanjungsari Village. Success Indicators: (a) Partners are able to create product innovations in processing and packaging of rabbit floss which is a unique potential of Tanjungsari Village; (b) Partners are able to create product innovations in packaging for UMKM products in Tanjungsari Village, and (c) Partners are able to utilize digital market place technology shopee and social media for promotion and marketing of UMKM products in Tanjungsari Village.